2019
DOI: 10.1038/s41598-019-47907-w
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Microbial Volatile Organic Compounds for Detection of Disease in Cattle: Development of Lab-scale Method

Abstract: The primary hurdle for diagnosis of some diseases is the long incubation required to culture and confirm the presence of bacteria. The concept of using microbial VOCs as “signature markers” could provide a faster and noninvasive diagnosis. Finding biomarkers is challenging due to the specificity required in complex matrices. The objectives of this study were to (1) build/test a lab-scale platform for screening of microbial VOCs and (2) apply it to Mycobacterium avium paratuberculosis ; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The diagnosis of mycobacterial infection is currently at the center of attention because, although well-established and reliable, it has its own limitations. Apart from being a tedious process, special consideration must be given to the lack of an optimal diagnostic sensitivity (Table 2) and the different variables which may interfere with the methods and techniques in use (2,21). Therefore, an accurate and reliable diagnostic methodology of the infection by mycobacteria, or a combination of various strategies, is the cornerstone of their control (23).…”
Section: Routine Diagnostic Techniques Against Mtbc and M Avium Subsp Paratuberculosismentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis of mycobacterial infection is currently at the center of attention because, although well-established and reliable, it has its own limitations. Apart from being a tedious process, special consideration must be given to the lack of an optimal diagnostic sensitivity (Table 2) and the different variables which may interfere with the methods and techniques in use (2,21). Therefore, an accurate and reliable diagnostic methodology of the infection by mycobacteria, or a combination of various strategies, is the cornerstone of their control (23).…”
Section: Routine Diagnostic Techniques Against Mtbc and M Avium Subsp Paratuberculosismentioning
confidence: 99%
“…Although IST and IFN-γ assay have reasonable sensitivity and good specificity (Table 2), both techniques require a minimum of 48-72 h to obtain a result (21, 65) besides presenting other disadvantages and limitations. On the one hand, IST requires visiting the farm and restraint of the animals twice, and a delicate and difficult administration and interpretation of skin results, which may vary due to differences in tuberculin doses, site of application (Table 2), and interpretation schemes (25, 27, 66); on the other hand, IFN-γ assay implies a complex laboratory methodology (18), a considerably more expensive price than a skin test (65,67), and suffers from cross-reactivity with other related mycobacteria resulting in false-positive results (2). In addition, performance of these tests can be compromised by factors associated with the immune response and health status of the animal leading to a misinterpretation of the results.…”
Section: Routine Diagnostic Techniques Against Mtbc and M Avium Subsp Paratuberculosismentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of VOCs has been identified over mycobacterial cultures, especially M. tuberculosis (Mtb) and M. bovis strains. Most of the substances described in our study were already reported previously ( 56 ). However, the knowledge about the origin and fate of VOCs within the metabolism of MAP is still limited.…”
Section: Discussionmentioning
confidence: 64%
“…paratuberculosis , Mycobacterium bovis ( M. bovis ) Bacillus Calmette‐Guérin and Mycobacterium kansasii bacteria from cattle cultured in bottles were collected with an SPME fiber for 1 h at 37 °C. [ 62 ] For obtaining the dynamic headspace, air at an average flow rate of 162 mL min –1 passed through each culture bottle in ≈13 mL closed loops made from PTFE Teflon tubing that went from the pump to the culture bottle, then to the sampling bulb, and back to the pump. The inlet and outlet fittings on each culture bottle included 0.22 µm filters to prevent the introduction of mycobacteria into the closed loop system.…”
Section: Voc Samples Collectionmentioning
confidence: 99%